The impact of COVID-19 on patients with epilepsy - Gloria Maria de Almeida Souza TEDRUS; João Fernando Cloclet Pio da SILVA; Gabriel Santaterra BARROS (Arquivos de Neuro-Psiquiatria)
ABSTRACT Background: The COVID-19 pandemic and social distancing can have adverse impacts on adult people with epilepsy (PWE). Objective: To investigate the seizure frequency, the perceived well-being, and the presence of anxiety symptoms in PWE during the COVID-19 pandemic period. Methods: Data from a questionnaire on the repercussions of COVID-19 were analyzed in relation to the clinical variables of 114 PWE, with a significance level of p<0.05. Results: There were 26 cases of COVID-19 in PWE and/or family members (22.8%). During the pandemic period, 11 PWE (9.6%) reported an increase in seizures, but unrelated to COVID-19. Also, the number of crises in PWE with previous depressive disorders increased, with differences between epilepsies. Symptoms of depression, impaired well-being, and concern for their lifestyle were significant in PWE with a previous diagnosis of depression. Impaired well-being, increased anxiety, nervousness, and tiredness, and the concern with being infected were mentioned by a high number of PWE in the pandemic. Conclusion: Seizure frequency increased during the pandemic period, a finding associated with clinical variables of epilepsy. PWE with depression had worse perceived well-being. Changes in well-being and increased anxiety and nervousness were frequent in the pandemic.